The Colonization of Synthetic Microbial Communities Carried by Bio-Organic Fertilizers in Continuous Cropping Soil for Potato Plants - Wenming Zhang; Shiqing Li; Pingliang Zhang; Xuyan Han; Yanhong Xing; Chenxu Yu (Microorganisms)
Synthetic microbial communities (SynComs) play significant roles in soil health and sustainable agriculture. In this study, bacterial SynComs (SCBs) and fungal SynComs (SCFs) were constructed by selecting microbial species that could degrade the potato root exudates associated with continuous cropping obstacles. SCBs, SCFs, and SCB + SCF combinations were then inoculated into organic fertilizers (OFs, made from sheep manure) to produce three bio-organic fertilizers (BOFs), denoted by SBFs (BOFs of inoculated SCBs), SFFs (BOFs of inoculated SCFs), and SBFFs (BOFs of inoculated SCB + SCF combinations), respectively. The OF and three BOFs, with a chemical fertilizer (CK) as the control, were then used in pot experiments involving potato growth with soil from a 4-year continuous cropping field. Microbial diversity sequencing was used to investigate the colonization of SCBs and SCFs into the rhizosphere soil and the bulk soil, and their effects on soil microbial diversity were evaluated. Source Tracker analysis showed that SCBs increased bacterial colonization from the SBFs into the rhizosphere soil, but at a relatively low level of 1% of the total soil bacteria, while SCFs increased fungi colonization from the SFF into the bulk soil at a much higher level of 5–18% of the total soil fungi. In combination, SCB + SCF significantly increased fungi colonization from the SBFF into both the bulk soil and the rhizosphere soil. Overall, the soil fungi were more susceptible to the influence of the BOFs than the bacteria. In general, the application of BOFs did not significantly change the soil microbial alpha diversity. Correlation network analysis showed that key species of bacteria were stable in the soils of the different groups, especially in the rhizosphere soil, while the key species of fungi significantly changed among the different groups. LEfSe analysis showed that the application of BOFs activated some rare species, which were correlated with improvements in the function categories of the tolerance of stress, nitrogen fixation, and saprotroph functions. Mantel test analysis showed that the BOFs significantly affected soil physicochemical properties, influencing bacterial key species, and core bacteria, promoting potato growth. It was also noted that the presence of SynCom-inoculated BOFs may lead to a slight increase in plant pathogens, which needs to be considered in the optimization of SynCom applications to overcome continuous cropping obstacles in potato production.